2023
DOI: 10.2138/am-2022-8142
|View full text |Cite
|
Sign up to set email alerts
|

Trace element and isotopic (S, Pb) constraints on the formation of the giant Chalukou porphyry Mo deposit, NE China

Abstract: Porphyry type Mo deposits have supplied most of the Mo to the world. However, the source of the Mo and the controls on its enrichment in such deposits is still a matter of great debate. In this study, we present in situ trace element and isotopic data for a giant porphyry Mo deposit (the Chalukou Mo deposit in NE China) and use these data to address these issues. Three primary paragenetic stages of mineralization were recognized at Chalukou: (I) K-feldspar + quartz + minor pyrite (Py-I) + minor molybdenite (Mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 82 publications
(44 reference statements)
0
2
0
Order By: Relevance
“…The northern margin of the NCC records a complicated series of geodynamic events (e.g., Xiao et al 2003;Zhang et al 2010;Wu et al 2011;Xu B et al 2013;Xu W et al 2013;Wilde 2015), with the formation of numerous different types of ore deposits during subsequent stages of tectonic evolution in the region (Zhao et al 2021a(Zhao et al , 2023Hong et al 2021;Zhai et al 2019Zhai et al , 2020. Widespread Permian intrusive rocks include monzonite, granite porphyry, granodiorite (280 Ma; Zhang et al 2020), biotite adamellite (274-268 Ma;Xiao et al 2012), and minor gabbro (279 Ma;Liu et al 2019).…”
Section: Regional Geologymentioning
confidence: 99%
“…The northern margin of the NCC records a complicated series of geodynamic events (e.g., Xiao et al 2003;Zhang et al 2010;Wu et al 2011;Xu B et al 2013;Xu W et al 2013;Wilde 2015), with the formation of numerous different types of ore deposits during subsequent stages of tectonic evolution in the region (Zhao et al 2021a(Zhao et al , 2023Hong et al 2021;Zhai et al 2019Zhai et al , 2020. Widespread Permian intrusive rocks include monzonite, granite porphyry, granodiorite (280 Ma; Zhang et al 2020), biotite adamellite (274-268 Ma;Xiao et al 2012), and minor gabbro (279 Ma;Liu et al 2019).…”
Section: Regional Geologymentioning
confidence: 99%
“…Therefore, it is suggested that the granodiorite related to Pb-Zn ore bodies might provide a basis for the source of bismuth in this ore district. Sulfur isotope composition can be used to distinguish different sulfur sources and is widely used to constrain the genesis of mineral deposits [21][22][23]. The sulfur isotope data (−3.8‰ to −1.4‰) for the Niuxingba-Liumukeng deposit reflect a possible magmatic source for the sulfur contained within metal sulfides [5].…”
Section: The Possible Source Of Bismuthmentioning
confidence: 99%